An ionic receptor for Zn2+ metal ion using synthesised bis-formylpyrazole calix[4]arene and its computational study. Issue 7 (3rd July 2018) - Mohan, Brij; Modi, Krunal; Bhatia, Pankaj; Sharma, H. K.; Mishra, Divya; Jain, Vinod K.; Arora, Lakhbeer Singh
Abstract: Newly synthesised receptor Bis-(1, 3-diphenyl-pyrazolyl methylene acetohydrazide)Calix[4]arene (DPPMACA) was evaluated for cation binding ability. The receptor DPPMACA selectively interact with Zn 2+ metal ion as assessed through UV-visible spectroscopy with a bathochromic shift of 14 nm but gave negligible response for other metal cations used as their sulfates. The stoichiometry observed as 1:1 with stability constant 6.438 × 10 3 M −1 . Additionally, computational visions were concentrated for studying the stability and spectroscopic analysis of the DPPMACA-Zn 2+ complex using docking, molecular dynamics simulations and density functional theory (DFT) along with time-dependent density functional theory (TD-DFT). The calculations significantly supplement the findings and elucidate the structural geometry and mode of interactions in supramolecular complexation. Herein, we witnessed that DPPMACA was selectively stabilized by Metal-donor and Metal-acceptor contacts with Zn 2+ to generate a low-energy complex. These findings are of wide interest, especially because Zn 2+ is a well-known biological important cation. Abstract :